Navigation for youth mental health and addictions: protocol for a realist review and synthesis of approaches and practices (The NavMAP standards project). Issue 11 (4th November 2022) - Markoulakis, Roula; Arora, Simran R A; Kodeeswaran, Sugy; Di Febo, Michelle; Kuuter, Liisa; Fleming, James; Walsh, Cathy; Hauser, Adina; Cleverley, Kristin; Hitzig, Sander L; Kokorelias, Kristina; Cheung, Amy; et al.
Abstract : Introduction: Mental health and/or addiction (MHA) concerns affect approximately 1.2 million children and youth in Canada, yet less than 20% receive appropriate treatment for these concerns. Youth who do not receive appropriate support may disengage from care and may experience lasting MHA issues. Families of these youth also support them in finding and accessing care. Thus, system supports are needed to help youth and their families find and equitably access appropriate care. Navigation is an innovation in MHA care, providing patient-centred support and care planning that helps individuals and families overcome barriers to care. Despite the increasing availability of navigation services for youth with MHA concerns, practices and models vary, and no single source has synthesised evidence regarding approaches and outcomes for this population into comprehensive standards. Methods and analysis: The proposed research will bring together evidence in youth MHA navigation, to establish this important system support as a factor that can enhance the integration and continuity of care for these youth. Our team, which includes researchers, administrators, clinical leads, an MHA navigator and youth and caregivers with lived experience, will be involved in all project stages. Realist Review and Synthesis methodology will be used, the stages of which include: defining scope, searching for evidence, appraising studies and extracting data, synthesising evidence and developing conclusions, and disseminating findings. Ethics and dissemination: Ethics approval is not required, as the study involves review of existing data. Dissemination plans include scientific publications and conferences and online products for stakeholders and the general public.